O espaço discursivo de divulgação religiosa na delimitação do estilo de totalidades antagônicas - Silva, Sueli Maria Ramos da (Estudos Semióticos, 2008)
We propose to consider how and why we can deduce two different and controversial ways of presence in the world, the style (ethos) and (antiethos) of two confronting enunciative scenes, A (Catholicism) and B (Jeovah’s witneses), from texts which materialize the religious divulgation discursive space.